Next door - Jahnavi Barua (UK Penguin Books, 2008)
In eleven superbly crafted stories Jahnavi Barua takes us into the private individual worlds of a varied cast of characters and exposes the intricate mesh of emotions so often concealed under the facade of everyday lives. Innocent desires and furtive longings the complexity of fierce love and the terrible consequences of its betrayal, simple aspirations that compel brave action lie's startling reversals that reveal deep insecurities and yet pave the way for forgiveness and recondition these are just some of the themes played out in these remarkably nuanced snapshots of life.redominantly set in the verdant, politically charged landscape of Assam, yet constantly transcending the particular, the stories in Next Door are unerringly human. Subtle and evocative in their telling, they mark the introduction of a highly accomplished voice.
Keywords: English Literature